N,N `-Bis[(E)-(5-chloro-2-thienyl)methylidene]ethane-1,2-diamine - Prasath, R.; Bhavana, P.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The full molecule of the title compound, C12H10Cl2N2S2, is generated by the application of a centre of inversion. The thiophene and imine residues are co-planar [the N-C-C-S torsion angle is -2.5 (4)degrees] and the conformation about the imine bond [1.268 (4) angstrom] is E. Supramolecular arrays are formed in the bc plane via C-Cl center dot center dot center dot pi interactions and these stack along the a axis